Method for Detection of Failures in Complex Process Control Systems - Portnov, Evgeni M.; Kyaw Zin Lin; Kokin, Vitaliy V.; Aung Kyaw Myo (2017 IVth International Conference on Engineering and Telecommunication (EnT), 2017)
At present automatic control systems and control of distributed power facilities are complex technical systems, in which include large number of elements and have complex structure. Automated system of management of technical process (ASMTP) is a group of solutions of hardware and software designed to automate control of technological equipment in industrial enterprises.